Geographic Information System of Informatics Alumni Distribution Using Fuzzy Method (case Study: UPN "Veteran" Jawa Timur) - Firya Nadhira; Chrystia Aji Putra; Hendra Maulana (JEECS (Journal of Electrical Engineering and Computer Sciences), 2021)
The alumni association is an important organization in a higher education institution. Apart from being a forum for communication between graduates, alumni associations also play a major role in providing information related to career opportunities, as a medium for exchanging training information and knowledge. Informatics Study Program at UPN "Veteran" Jawa Timur already has an alumni association called IKATIFA (Ikatan Alumni Teknik Informatika). Although there is already an IKATIFA information system, the website does not have a specific system regarding alumni information in the world of work. By utilizing Geographic Information System (GIS) can present data specifically by using a map as an interface. In this research, alumni clustering was carried out using a fuzzy algorithm. There are 3 clusters, cluster 1 mean alumni work fields existing is according to study program competency, cluster 2 mean alumni work fields existing is almost according to study program competency, cluster 3 mean alumni work fields existing is not in accordance with study program competency. The test results on the testing data show that as many as 62% alumni work fields existing is according to study program competency, as many as 18% alumni work fields existing is almost according to study program competency, and as many as 20% alumni work fields existing is not in accordance with study program competency.